2018
DOI: 10.3390/ijerph15020355
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical and Empirical Linkage between Road Accidents and Binge Eating Behaviors in Adolescence

Abstract: This study aimed at identifying specific clusters of maladaptive emotional–behavioral symptoms in adolescent victims of motorbike collisions considering their scores on alexithymia and impulsivity in addition to examining the prevalence of clinical binge eating behaviors (respectively through the Youth Self-Report (YSR), Toronto Alexithymia Scale-20 (TAS-20), Barratt Impulsiveness Scale-11 (BIS-11), and Binge Eating Scale (BES)). Emotional–behavioral profiles, difficulties in identifying and describing feeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 64 publications
(71 reference statements)
4
7
0
Order By: Relevance
“…(2) The possible associations between MVCs, alexithymic traits, and maladaptive defense strategies use. We hypothesized that a higher rate of MVCs is associated with higher emotional difficulties in terms of alexithymia and significant use of immature defense strategies, in line with previous studies in the field [ 63 , 64 , 85 ]. (3) Possible mediation role played by adolescents’ maladaptive defense strategies use in the relationship between alexithymia and frequencies of MVCs.…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…(2) The possible associations between MVCs, alexithymic traits, and maladaptive defense strategies use. We hypothesized that a higher rate of MVCs is associated with higher emotional difficulties in terms of alexithymia and significant use of immature defense strategies, in line with previous studies in the field [ 63 , 64 , 85 ]. (3) Possible mediation role played by adolescents’ maladaptive defense strategies use in the relationship between alexithymia and frequencies of MVCs.…”
Section: Introductionsupporting
confidence: 64%
“…Only a few studies have explored the possible individual vulnerabilities that may predispose the adolescent to a higher risk of MVCs [ 57 , 58 , 59 , 60 ]. In this field, clinicians and researchers rooted in the Developmental Psychopathology framework [ 61 , 62 ] have suggested that the presence of adolescents’ emotional difficulties preceding the accidents may lead to a higher risk of a MVC [ 63 , 64 , 65 ], as a form of acting out to cope with underlying psychological sufferance [ 66 , 67 , 68 ]. Some studies have focused on clinical samples of adolescents, evidencing significant associations between MVCs and ADHD [ 69 ], depression [ 70 ], personality disorders [ 71 ], and binge eating disorder [ 64 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traumatic events can predispose adolescents to develop symptoms of depression and/or other psychiatric disorders. For instance motor vehicle accidents can induce maladaptive behaviors in children including a disturbed eating patterns which might be a reflection of psychological difficulties and emotional dysregulation [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, during the specific evolutionary phase of adolescence, characterized by different physical, biological, psychological and social changes [19,20], individuals become especially vulnerable to suffer some problems specifically identified as eating disorders [21,22] or addictive disorders [23].…”
Section: Introductionmentioning
confidence: 99%